River Wyre salmon and sea trout spawning habitat restoration / creation project. Final report April 1995 - APEM (APEM, 1995)
Adult salmon and sea trout rod catches in the River Wyre have been subject to considerable variability over the years. Annual rod catches ranging from 6 to 401 have been reported since records began in 1905. It has long been suspected that the physical nature of the catchment, combined with anthropogenic influences, has resulted in a deleterious effect on the Wyre fishery. Acidification problems in the head water streams (Marshaw Wyre and Tarnbrook Wyre) have been reported and are thought to threaten salmon juvenile survival. The construction of Abbeystead Reservoir and an increased tendency towards rapidly rising water levels during storms (flashiness)1 are thought to have a significant impact on spawning gravel quality and quantity, both of which are thought to be deteriorating. As part of an overall desire to maintain and improve the migratory salmonid population in the River Wyre, this project has been commissioned to investigate remedial action which may improve and enhance spawning success, leading to an eventual improvement in the status of adult stocks. The primary objective is to establish whether the quantity and/or quality of available spawning gravels are limiting migratory salmonid productivity. The investigations undertaken confirm the general observation that useable spawning gravels appear to be in short supply in the River Wyre, and may be the limiting factor influencing returning adult stock. Environment Agency Archives North West